KAJIAN TEORITIS LAYANAN KONSELING UNTUK KORBAN KEKERASAAN DALAM RUMAH TANGGA (KDRT) - Maria Oktasari; Hayu Stevani; Solihatun Solihatun (Psikodidaktika, 2018)
Domestic violence is an act against someone especially women which resulted in the incidence of misery or suffering physical, psychological, sexual and/or abandonment of the household including the threat to doing the deed, coercion or deprivation of freedom are against the law in the sphere of the household (UU No. 23 Th 2004). The incidence of suffering physical, psychological, and sexual abuse on victims of domestic violence will have an impact on the lives of either not effective daily. Therefore, the impact of which must be overcome. There are several ways to help cope with the impact of, the one with the granting of domestic violence counselling services to the victims. Granting counselling service aims to help overcome the problems experienced by victims of domestic violence. How the shape of the counselling services provided for victims of domestic violence will be discussed in this paper.